2004
DOI: 10.1161/01.str.0000144684.46826.62
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Constipation and Fecal Incontinence in Stroke Patients

Abstract: Background and Purpose-Despite its high prevalence in stroke survivors, there is little clinical research on bowel dysfunction in this population. This is the first randomized controlled trial to evaluate treatment of constipation and fecal incontinence in stroke survivors. Methods-Stroke patients with constipation or fecal incontinence were identified by screening questionnaire (122 community, 24 stroke rehabilitation inpatients) and randomized to intervention or routine care (73 per group). The intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(66 citation statements)
references
References 29 publications
0
60
0
3
Order By: Relevance
“…Thus, in the literature, the prevalence of intestinal constipation in patients suffering from stroke sequelae can range between 22.9% a 60%, although different definitions and research phases are identified in the studies. In some cases, prevalence rates were investigated in more acute patients or after a recent injury [10][11]19 and in others with chronic patients. 9,13 In the present study, this difference can be justified by the method -retrospective analysis of electronic patient chart -and the consequent impossibility to investigate other intestinal constipation symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in the literature, the prevalence of intestinal constipation in patients suffering from stroke sequelae can range between 22.9% a 60%, although different definitions and research phases are identified in the studies. In some cases, prevalence rates were investigated in more acute patients or after a recent injury [10][11]19 and in others with chronic patients. 9,13 In the present study, this difference can be justified by the method -retrospective analysis of electronic patient chart -and the consequent impossibility to investigate other intestinal constipation symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of intestinal constipation in patients with brain injury secondary to CVA ranges between 22.9% and 60%, depending on the definition used and the type of study. [9][10][11] Anal incontinence, on the other hand, can vary between 30% and 40% in the acute phase and between 9% and 15% in the chronic phase.…”
Section: Introductionmentioning
confidence: 99%
“…Bowel dysfunction are the most frequent gastrointestinal complaints with a negative impact on patients' quality of life, restricting their social activities (Bracci et al, 2007;Su et al, 2009). The prevalence of constipation after stroke varies from 30% to 60% (Harari et al, 2004). New-onset constipation is seen in 55% of patients within a month after first stroke, strongly relating to disability.…”
Section: Constipation In Strokementioning
confidence: 99%
“…It does not lead to decrease in laxative intake, so abdominal massage could be a complement to medication rather than a substitute (Lämås et al, 2009 Kumar et al, 2010). A systematic assessment of bowel habits by nursing staff with a simple practice-based approach towards bowel management and patient/caregiver education has been shown to be helpful in patients with stroke (Harari et al, 2004).…”
Section: Management Of Constipation In Neurological Disordersmentioning
confidence: 99%
“…However, very little attention has been paid to gastrointestinal motility in autonomic function after stroke. Constipation is recognized as a serious problem in clinical practice, affecting 60% of stroke rehabilitation ward attendees [4]. Although Bracci et al [5] reported that constipation is due to neurological lesions and is unrelated to age, gender and physical inactivity, the mechanism of constipation after stroke has not thus far been well-studied.…”
Section: Introductionmentioning
confidence: 99%